Gambus Misri sebagai Kesenian Islam di Jombang - Devi, Rahadian Masfufah; Masyhudi, Masyhudi (Qurthuba: The Journal of History and Islamic Civilization, 2023)
This article aims to explore Gambus Misri in Jombang Regency from a historical perspective. Gambus Misri which is an art form resulting from acculturation of Islam and culture whose existence contains its own elements, meanings and values for the people of Jombang. This study uses historical research methods with a diachronic approach. The analytical knife used in this research is cognitive anthropological theory developed by Ward. H. Goodenough. The results of this study can be concluded that: 1) Jombang Regency has a Muslim majority population with traditional arts which are identical with the santri community. In Gambus Misri, which pours out various combinations of music, dance, acting, jokes and religion, in which the religion contains several meanings of advice and preaching to invite goodness. 2) Art revitalized by STKIP PGRI Jombang students as an effort to revive this dead art. There were several efforts and preparations before, during and after the Gambus Misri performance. 3) Gambus Misri tides cause several changes, including; the development of players, the development of musical instruments, and there are values contained in them such as; changes in the value of Gambus Misri actors and technology transfer without changing the standard of Gambus Misri.